A post-racial change is gonna come : Newark, Cory Booker, and the Transformation of Urban America - Wharton, Jonathan L.; SpringerLink (Online service). (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
An investigation of post-racial politics and the future of coalition politics in an American city.
Keywords: Science